LIKUIDITAS DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Rahman, Alrival Zainur; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Progress and competition in economic conditions in the business world are increasingly experiencing faster growth. Pharmaceutical companies have high potential in the industrial sector to supporting the Indonesian economy and are able to continue to contribute to increasing industrial growth in the health sector for social welfare in Indonesia. The purpose of this study is to analyze and test the Liquidity and Asset Structure of Capital Structure in Pharmaceutical Companies Listed on the Indonesia Stock Exchange with Profitability as an Intervening Variable. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis testing using the Smart PLS 3.0 application, show that Liquidity has a negative but insignificant effect on Profitability. Asset structure has a negative but insignificant effect on Profitability. Liquidity has a negative but insignificant effect on capital structure. Asset structure has a positive but insignificant effect on capital structure. Profitability has a significant negative effect on capital structure. The results of the indirect hypothesis test show that Liquidity has a positive but insignificant effect on capital structure through Profitability. Asset structure has a positive but insignificant effect on capital structure through Profitability.